2018
DOI: 10.1016/j.ipm.2017.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Discourse-aware rumour stance classification in social media using sequential classifiers

Abstract: Rumour stance classification, defined as classifying the stance of specific social media posts into one of supporting, denying, querying or commenting on an earlier post, is becoming of increasing interest to researchers. While most previous work has focused on using individual tweets as classifier inputs, here we report on the performance of sequential classifiers that exploit the discourse features inherent in social media interactions or 'conversational threads'. Testing the effectiveness of four sequential… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
87
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
2

Relationship

3
7

Authors

Journals

citations
Cited by 128 publications
(102 citation statements)
references
References 56 publications
0
87
0
Order By: Relevance
“…Additional labels can then be added to the datasets to better predict veracity, for instance by jointly training stance and veracity prediction models. Methods not shown in the table, but related to fact checking, are stance detection for claims (Ferreira and Vlachos, 2016;Pomerleau and Rao, 2017;Augenstein et al, 2016a;Kochkina et al, 2017;Augenstein et al, 2016b;Zubiaga et al, 2018;Riedel et al, 2017), satire detection (Rubin et al, 2016), clickbait detection (Karadzhov et al, 2017), conspiracy news detection (Tacchini et al, 2017), rumour cascade detection (Vosoughi et al, 2018) and claim perspectives detection (Chen et al, 2019).…”
Section: Datasetsmentioning
confidence: 99%
“…Additional labels can then be added to the datasets to better predict veracity, for instance by jointly training stance and veracity prediction models. Methods not shown in the table, but related to fact checking, are stance detection for claims (Ferreira and Vlachos, 2016;Pomerleau and Rao, 2017;Augenstein et al, 2016a;Kochkina et al, 2017;Augenstein et al, 2016b;Zubiaga et al, 2018;Riedel et al, 2017), satire detection (Rubin et al, 2016), clickbait detection (Karadzhov et al, 2017), conspiracy news detection (Tacchini et al, 2017), rumour cascade detection (Vosoughi et al, 2018) and claim perspectives detection (Chen et al, 2019).…”
Section: Datasetsmentioning
confidence: 99%
“…BranchLSTM: a method based on an LSTM layer followed by several dense ReLU layers and a softmax layer (Zubiaga et al, 2018b).…”
Section: Compared Methodsmentioning
confidence: 99%
“…Research has shown that leveraging the temporal component and the evolving discourse around news stories is important to determine the stance of individual posts. Zubiaga et al [125] conducted a comprehensive study comparing different sequential classifier to mine the discursive structure of social media information, finding that a Long-Short Term Memory network (LSTM) performed best, outperforming Conditional Random Fields (CRF) and Hawkes Processes.…”
Section: Other Tasksmentioning
confidence: 99%